Answer:
w=10
Step-by-step explanation:
1. Divide 4 on both sides to cancel out the 4 on the right side since it is an equation so it has to remain “equal”/ balanced.
2. You get 7=w-3.
3. Add 3 on both sides.
4.You get w=10.
Answer:
(f-g)(x) = x-3
Step-by-step explanation:
Given
f(x) = 3x-2
and
g(x) = 2x+1
We have to find (f-g)(x)
So,
(f-g)(x) = f(x)-g(x)
= 3x-2 - (2x+1)
= 3x-2-2x-1
=x-3
Hence,
(f-g)(x) = x-3
Answer:
So first, you have to isolate w. You can do this by getting rid of the 8/5.
This will get you to: w = 25
Answer:
$33012
Step-by-step explanation:
Total Monthly Budget= $ 2751
Total Yearly Budget=2751×12=$33012
Answer:
It is B
Step-by-step explanation:
It is the graph of f (x) reflected about the x-axis and shrunk vertically by a factor of 10.